Comparative analysis of family businesses with non-family businesses: empirical evidence from India - Kota, Hima Bindu; Singh, Ramanjeet (Serbian Journal of Management, 2016)
Family businesses are fundamental to nation building as they contribute towards the GDP of any country and are also major employment creators. Therefore, family business management is an emerging area of academic interest. In this regard, comparison between family and non-family businesses has become an important area of research. The present study analyses the performance of Indian family businesses in comparison to non-family business for firms listed on BSE 500 Index for a period of 11 years from 2005-2015. Any firm with 40% or more promoter or promoter group holding has been identified as a family business. Performance of family businesses was measured across 5 categories, viz, Profitability, Size, Market Position, Debt Position and Number of Employees. Within these 5 categories, comparison was done on the following 12 variables like Return on Net Worth (RONW), Return on Capital Employed (ROCE), Return on Total Assets (ROTA), Firm Size (SIZE), Total Assets (ASSETS), Total Revenue (REV), Market Capitalization (MACP), Current Ratio (CR), Quick Ratio (QR), Debt-Equity Ratio (DER), Interest Coverage Ratio (INTCOV) and Number of Employees (EMP), using independent t- test. It was found that in the Indian context, non-family business outperform family businesses in all 5 categories studied. Key Words: Family Businesses, Performance, Profitability, Market Capitalization, Debt Position JEL Classification: M00